Resistência de tomateiros mutantes a Bemisia tabaci(Gennadius, 1889)(Hemiptera: Aleyrodidae) biótipo B e influência sobre Encarsia hispida(Hymenoptera: Aphelinidae) - Souza, Mileny dos Santos de (2019)
The tomato is one of the most cultivated and consumed vegetables in the world, however it is considered a high risk crop when we consider the large number of phytosanitary problems in which it is affected. Being the whitefly Bemisia tabaci biotype B, one of these main problems, given the damages and the cost of control that is inserted in its production. The use of resistant cultivars associated to biological control within an Integrated Pest Management program can act as one of the best solutions to problems with this pest, since the reduction or elimination of control with pesticides. In view of the above, the general objective of this research was to determine if mutant tomatoes confer resistance to Bemisia tabaci biotype B and its influence on the parasitoid Encarsia hispida. The research was carried out in the Laboratory of Entomology of the Federal University of Paraiba, Campus II Areia-PB, addressing in three articles to the topics explained above. The performance of five mutant tomatoes (aurea, cry, phyA, phyB1, phyB2) plus one susceptible standard tomato ('IAC-Santa Clara') were evaluated in a greenhouse and field environment. Article I: The objective of this study was to determine if mutant tomatoes confer resistance to B. tabaci biotype B. In the free choice test (TLE), the number of eggs, nymphs and adults / plants was measured and, furthermore, the index of attractiveness (AI) and the index of preference for IPO oviposition, colonization of nymphs, damage and growth of fumagina. The number of eggs, IPO, insect biology and number of trichomes were measured in the non-choice test (TSE). In the TLE, the standard cultivar presented higher number of eggs, nymphs and adults, higher IPA, IPO, damage and growth of the fumagina, besides high colonization of nymphs and low number of trichomes. In the TLE the aurea provided the largest and the standard cultivar the shortest number of days to complete the insect biology. The aurea presents resistance type antibiosis and antixenosis, less damages to the plants and less growth of the fumagina when infested by B. tabaci biotype B. Article II: The biochemical and physiological behavior of mutant tomatoes against the B. tabaci biotype B attack was verified by measuring the number of eggs, nymphs and adults of the pest after three periods of infestation and the activity of POX, PPO and PAL enzymes as well as the physiological variables A, E, gs, Ci, iWUE, EiC and WUE, fluorescence, chlorophyll and number of trichomes. The mutants presented lower infestation and colonization of the pest; increased activity of oxidative enzymes; and less wear the physiology against the attack of B. tabaci when compared to 'Santa Clara'. The aurea confers greater resistance, activates its biochemical defense mechanisms, and suffers less physiological damage in the face of B. tabaci infestation. Article III: The objective was to investigate the tritrophic interaction between mutant tomatoes, B. tabaci biotype B and the parasitoid Encarsia hispida. Tomatoes were used as hosts of the pest, and the 3rd and 4th instar nymphs were submitted to the parasitism of E. hispida. It was evaluated the biological development of the parasitoid and also the natural parasitism index and under releases of this agent. The biological development of the parasitoid was not affected by the mutant tomatoes, as well as the longevity and the sexual ratio. As for the parasitism, the index was higher in protected environment, the mutant aurea and the standard cultivar with the highest values, already in the field no differences were observed among tomato plants. Mutants provide adequate biological development to the parasitoid; the rate of parasitism is higher when the parasitoid is released; aurea and ‘Santa Clara’ have higher rates of parasitism.